Physiological and Functional Assessment of Professional Football Players - Hoyo, Moisés de; Sañudo, Borja; Taiar, Redha; Páez, Luis Carrasco (Routledge, 2025)
Physiological and Functional Assessment of Professional Football Players presents a science-based approach to enhance athletes' performance and prevent muscle injuries. Professional football players undergo a rigorous competitive season with frequent and numerous competitions, exposing them to significant stress that can detrimentally affect their performance and lead to serious injuries in extreme cases. In order to avert such negative outcomes, coaches and team staff must formulate preventive training programs tailored to the unique characteristics and needs of each player. The execution of these individualized training programs necessitates a comprehensive assessment of players' health status, evaluation of their functional and fitness performance, analysis of their muscular structure, identification of muscle imbalances or movement dysfunctions, and detection of potential injury risk factors. Furthermore, it is imperative to monitor the weekly training and competition load using appropriate indicators of external and internal load, adjusting workloads accordingly. In addition, recovery training programs must be meticulously designed for each injured player. This process involves isolating the factors causing the injury and assessing the injury's severity in the initial stage. Subsequently, recovery training programs must be thoughtfully planned, incorporating various assessment tools and procedures to verify the restoration of players' functional ability and inform decisions about the return to play. Physiological and Functional Assessment of Professional Football Players delves into the utilization of appropriate testing protocols and emphasizes that understanding the reported data is crucial for the success of professional football training. This groundbreaking book is essential reading for researchers and practitioners in the fields of soccer, sports science, recovery, data and performance analysis, and soccer coaching.